Repair of sub-lethal freezing damage in leaves of Arabidopsis thaliana - Vyse, Kora (BMC Plant Biol, 2020)
BACKGROUND: The detrimental effects of global climate change direct more attention to the survival and productivity of plants during periods of highly fluctuating temperatures. In particular in temperate climates in spring, temperatures can vary between above-zero and freezing temperatures, even during a single day. Freeze-thaw cycles cause cell membrane lesions that can lead to tissue damage and plant death. Whereas the processes of cold acclimation and freeze-thaw injury are well documented, not much is known about the recovery of plants after a freezing event. We therefore addressed the following questions: i. how does the severity of freezing damage influence repair; ii. how are respiration and content of selected metabolites influenced during the repair process; and iii. how do transcript levels of selected genes respond during repair? RESULTS: We have investigated the recovery from freezing to sub-lethal temperatures in leaves of non-acclimated and cold acclimated Arabidopsis thaliana plants over a period of 6 days. Fast membrane repair and recovery of photosynthesis were observed 1 day after recovery (1D-REC) and continued until 6D-REC. A substantial increase in respiration accompanied the repair process. In parallel, concentrations of sugars and proline, acting as compatible solutes during freezing, remained unchanged or declined, implicating these compounds as carbon and nitrogen sources during recovery. Similarly, cold-responsive genes were mainly down regulated during recovery of cold acclimated leaves. In contrast, genes involved in cell wall remodeling and ROS scavenging were induced during recovery. Interestingly, also the expression of genes encoding regulatory proteins, such as 14–3-3 proteins, was increased suggesting their role as regulators of repair processes. CONCLUSIONS: Recovery from sub-lethal freezing comprised membrane repair, restored photosynthesis and increased respiration rates. The process was accompanied by transcriptional changes including genes encoding regulatory proteins redirecting the previous cold response to repair processes, e.g. to cell wall remodeling, maintenance of the cellular proteome and to ROS scavenging. Understanding of processes involved in repair of freeze-thaw injury increases our knowledge on plant survival in changing climates with highly fluctuating temperatures.